Kinetic Modeling of Biomass Steam Gasification System for Hydrogen Production with CO2 Adsorption - Inayat, Abrar; Ahmad, Murni M; Abdul Mutalib, M I; Yunus, Mohd Khairuddin (2009)
Due to energy and environmental issues, hydrogen becomes a more attractive clean fuel. There is high interest to produce hydrogen from biomass in view of sustainability. The thermo chemical process i.e. gasification is highlighted for hydrogen production. This paper discusses the mathematical modeling of hydrogen production through steam gasification with calcium oxide as sorbent in one gasifier. The model framework consists of kinetics model based on chemical reactions with few assumptions using MATLAB. This work investigates the influence of the temperature, steam/biomass ratio and sorbent/biomass ratio on the hydrogen and product gas composition. The importance of different reactions involved in the system is also discussed. The model helps to predict the product gas composition and hydrogen gas mole fraction from biomass. It is observed that at 1000 K temperature,3.0 steam/biomass ratio and 1.0 sorbent/biomass ratio maximum hydrogen mole fraction obtained in the product gas i.e. 0.82. At sorbent /biomass 1.52, purity of hydrogen is increased to 0.98 mole fraction with all CO2 present in system absorbed.